2018
DOI: 10.17219/acem/69261
|View full text |Cite
|
Sign up to set email alerts
|

TThe role of hypoxia-inducible factors in leukemias

Abstract: Hypoxia, understood as low partial oxygen pressure, has become one of the most explored fields in recent years. Cellular response to hypoxia is mediated by hypoxia-inducible factors (HIFs) -potent transcription regulators, and their downstream pathways. In general, HIFs modify energy metabolism, inflammation and immune response, enhance cancer invasion, metastasis, resistance to treatment, and relapse. The influence of HIFs on the progression of leukemia is still under investigation in various studies, but in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 54 publications
(68 reference statements)
0
4
0
Order By: Relevance
“…Activated HIFs lead to changes in the microenvironment that support tumor survival and growth, such as angiogenesis (Bousquet et al, 2016;Talks et al, 2000). In addition to the role of HIFs in solid tumors, HIF-mediated signaling has been found to play a crucial role in leukemia (Deynoux et al, 2016;Szymczak et al, 2018;Wang et al, 2011b). And activated KRAS has been shown to induce HIF1A and ARNT target genes expression in human colon cancer cells (Chun et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activated HIFs lead to changes in the microenvironment that support tumor survival and growth, such as angiogenesis (Bousquet et al, 2016;Talks et al, 2000). In addition to the role of HIFs in solid tumors, HIF-mediated signaling has been found to play a crucial role in leukemia (Deynoux et al, 2016;Szymczak et al, 2018;Wang et al, 2011b). And activated KRAS has been shown to induce HIF1A and ARNT target genes expression in human colon cancer cells (Chun et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…This model exhibits a dramatic increase of hemocyte numbers caused by over-proliferation, which provides an ideal phenotype for genetic and drug screens. Using this model in a genetic screen, we identified 24 promising hits that when silenced in the hemocytes, attenuated the Disease Models & Mechanisms • DMM • Accepted manuscript leukemia phenotype of the KRAS G12V model, including two key components of the hypoxia pathway, HIF1A and ARNT (HIF1B), which are involved in the development of both solid tumors and hematological malignancies (Deynoux et al, 2016;Jun et al, 2017;Semenza, 2003;Szymczak et al, 2018) . A drug screen using the same model revealed echinomycin, an inhibitor of HIF1A, could antagonize the KRAS G12V induced leukemia phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, patients diagnosed with type 2 diabetes have renal hypoxia, OS, endoplasmic stress, and a nutritional deficiency that will cause HIF-1α activation and HIF-2α suppression. Studies performed so far reported that high expression levels of HIFs are correlated with poor prognosis for various cancer types [ 4 , 51 , 52 , 53 , 54 ]. Pancreatic beta cells can be subjected to O 2 deprivation, so hypoxia can contribute to beta cells damage [ 55 ].…”
Section: Hypoxia-inducible Factors: Structure Roles and Involvement I...mentioning
confidence: 99%
“…On the other hand, O 2 deprivation induces stress in living cells, linked with free-radical accumulation and oxidative stress (OS) development [ 3 ]. Hypoxia is established when the overall oxygen pressure is less than 40 mmHg in cells or tissues [ 4 ]. However, tissues and cells have different degrees of hypoxia [ 5 ].…”
Section: Introductionmentioning
confidence: 99%